Language, exclusion and violent jihad: are they related?. Issue 6 (18th August 2018) - Samata, Susan
ABSTRACT: This paper advances the hypothesis that an inability to fully participate in an immigrant parent's first language as a minority community language, and associated pressures this can put on the individual's sense of personal identity and self-esteem, can be a contributing factor to the profound alienation that has been implicated in the rise of Islamic extremist violence. Studies of Islamic extremism have sought to identify common factors in the backgrounds of self-styled jihadists; however, they have proved to be a fairly heterogeneous group. One factor that stands out is that, in Europe and North America, the so-called home-grown terrorist is frequently a second- or third-generation immigrant. Education in the majority community language and a desire to assimilate not infrequently lead to an incomplete acquisition, and subsequent attrition of a 'home' language. This can separate the second/third-generation immigrant from the minority community, while discrimination forms a barrier to acceptance by the majority community. This paper briefly examines some of the background literature in Applied Linguistics and Counter Terrorism Studies, before turning to sources that tend to support the hypothesis. Finally, a case is made for further study and some possible approaches suggested.